Hyperuricemia in Down syndrome children and adolescents - Renato Nisihara; Pietro Massuda; Hatsuo Miyatake; Nanci Oliveira; Isabela Moreno; Thelma Skare
ABSTRACT Introduction: Patients with Down syndrome (DS) seem to have higher rates of hyperuricemia, although there are very few studies that address this issue. High levels of uric acid (UA) are an independent risk factor for atherosclerotic heart disease. Objective: To study the prevalence of hyperuricemia in DS children and its distribution according to age. Methods: Retrospective study of 139 DS patients aged 1-14 years for serum UA values considering the normal cut-off values for age. Results: Among the 139 included patients, 70 (50.4%) were males, 69 (49.6%) were females, and the mean age was 5.31 ± 3.49 years (range 1-14 years). In this sample, 39 (28.1%) had serum UA levels above the normal value. We did not find differences in the serum UA according to gender, except in patients in the range of 13-15 years, where males had mean UA levels of 5.75 ± 1.37 mg/dl; and females, of 8.02 ± 0.77 mg/dl (p = 0.02). Conclusion: We found a high rate of hyperuricemia in children with DS that equally affects both genders, except in the age range of 13-15 years, in which it was more common among females.